Rola armii lądowej a brytyjskie postulaty rozbrojenia lądowego 1919—1939 - Harasimowicz, Andrzej (Acta Universitatis Lodziensis. Folia Historica, 1983)
Disarmament programme was an essential element in the security policy pursued by the British government. This government had a sincere approach to disarmament; it neither wanted nor planned the war; practically — it carried out disarmament to a considerable degree, illogically relusing a guarantee of security to smaller states disarming themselves. The thesis put forward here is that the British government sincerely wished to preserve peace in Europe and trusted that disarmament policy might be useful, or at least it could reduce the aggression strength of other armies. Of great significance here were reasons of budgetary nature and unwillingness to base the League of Nations systems on guarantees and military sanctions.